A Study on Cough Sensitivity and Airway Inflammation in Patients with Sinobronchial Syndrome - Shengyuan Wang; Shanshan Niu; Siwan Wen; Mengru Zhang; Cuiqin Shi; Zhongmin Qiu; Li Yu; Xianghuai Xu (Canadian Respiratory Journal)
Objective. This study aimed to clarify the characteristics of cough-reflex sensitivity and airway inflammation in patients with sinobronchial syndrome (SBS). Methods. 39 patients with SBS, 53 patients with upper airway cough syndrome (UACS) induced by rhinitis, 33 patients with chronic sinusitis without cough, and 39 healthy controls (HCs) were enrolled between January 2013 and December 2018. All participants underwent a capsaicin cough-sensitivity test and cytology of induced sputum. The concentration of calcitonin-gene-related peptide (CGPR), histamine, prostaglandin (PG) E2, and eosinophil cationic protein (ECP) in induced sputum were measured using enzyme-linked immunosorbent assays (ELISAs). Results. The lowest concentration of capsaicin solution that induced ≥5 coughs (C5) was decreased markedly in patients with UACS induced by rhinitis compared with SBS patients (1.95 ± 2.92 vs. 31.2 ± 58.6 mol/L, P<0.001), indicating higher cough-reflex sensitivity among UACS patients induced by rhinitis. However, there was no difference of these threshold between SBS patients and patients with sinusitis without cough and HCs. The percentage of neutrophils in sputum was increased remarkably in patients with SBS compared with HCs (40.0 ± 48.5% vs. 5.5 ± 9.0%, P<0.001). A higher concentration of CGPR, histamine, and PGE2 was observed in induced sputum from patients with UACS induced by rhinitis than that in controls, and the ECP level was increased significantly in UACS induced by rhinitis compared with that in the other three groups. Conclusions. Cough-reflex sensitivity and airway inflammation in patients with SBS were different in patients with UACS induced by rhinitis. Thus, the mechanism of cough in those two patient populations might differ. Our study is registered in the Chinese Clinical Trials Register (https://www.chictr.org.cn/) as ChiCTR-TRC-00000152.